2015
DOI: 10.1002/cncr.29298
|View full text |Cite
|
Sign up to set email alerts
|

Predicting early mortality in resectable pancreatic adenocarcinoma: A cohort study

Abstract: BACKGROUND: Survival after surgical resection for pancreatic cancer remains poor. A subgroup of patients die early (<6 months), and understanding factors associated with early mortality may help to identify high-risk patients. The Khorana score has been shown to be associated with early mortality for patients with solid tumors. In the current study, the authors evaluated the role of this score and other prognostic variables in this setting. METHODS: The current study was a cohort study of patients who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…Kuderer et al retrospectively analyzed the 4405 patients involved in the original Khorana study and concluded KRS could predict early mortality (<120 days) and cancer progression. 14 In their cohort of resectable pancreatic adenocarcinoma, Sohal et al 13 also reported KRS was associated with early mortality (within 30 days), which is in line with the findings in lung cancer. 9 In the present cohort, however, KRS >0 was not associated with higher mortality in multivariate analysis.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Kuderer et al retrospectively analyzed the 4405 patients involved in the original Khorana study and concluded KRS could predict early mortality (<120 days) and cancer progression. 14 In their cohort of resectable pancreatic adenocarcinoma, Sohal et al 13 also reported KRS was associated with early mortality (within 30 days), which is in line with the findings in lung cancer. 9 In the present cohort, however, KRS >0 was not associated with higher mortality in multivariate analysis.…”
Section: Discussionsupporting
confidence: 63%
“…10 A modification of the KRS was externally validated in Vienna Cancer and Thrombosis Study 11 ; however, in subsequent cohorts of specific cancer types, the score has been challenged and deserves retesting. 9,12,13 In addition, it has been suggested that the KRS may add information on the prediction of mortality, 14 and this has not been tested in patients with hepatocellular carcinoma (HCC).…”
Section: Introductionmentioning
confidence: 99%
“…We are not the first to describe the KRS as a potential predictor of mortality. In a study of patients with pancreatic cancer, patients with a high KRS were more likely to die within 6 months (HR, 2.5; 95% CI, 1.1–2.1) . Similarly, in a prospective cohort of 1544 patients with different types of cancer the KRS was associated with risk of death (HR per increase of 1 point within the KRS, 1.6; 95% CI, 1.45–1.68).…”
Section: Discussionmentioning
confidence: 97%
“…However, some researchers found that median OS of patients with RPC was approximately 12 months after surgery alone [9]. Other researchers found that the median OS of patients with RPC was <2 years after surgery and adjuvant therapy [10, 11]. Furthermore, at least 25% of patients cannot receive adjuvant chemotherapy because of complications related to surgery [9].…”
Section: Introductionmentioning
confidence: 99%